60-6x=90-26x

Simple and best practice solution for 60-6x=90-26x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 60-6x=90-26x equation:


Simplifying
60 + -6x = 90 + -26x

Solving
60 + -6x = 90 + -26x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '26x' to each side of the equation.
60 + -6x + 26x = 90 + -26x + 26x

Combine like terms: -6x + 26x = 20x
60 + 20x = 90 + -26x + 26x

Combine like terms: -26x + 26x = 0
60 + 20x = 90 + 0
60 + 20x = 90

Add '-60' to each side of the equation.
60 + -60 + 20x = 90 + -60

Combine like terms: 60 + -60 = 0
0 + 20x = 90 + -60
20x = 90 + -60

Combine like terms: 90 + -60 = 30
20x = 30

Divide each side by '20'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| 7.5+0.5x=3x+1.5 | | 28=(16)-(4x) | | 3x(20-x)= | | -3+1=4*3-5-3*3 | | -14x+7y=-21 | | y-16=.25 | | -9x+30=-12 | | 8y^2+6y-35=0 | | -x-5=-2 | | X+(2X)+(X+2ft)=70 | | 10m+5=5 | | -x-2=-5 | | 9-2x=6x-15 | | 3(x-0.5x)-2x=132 | | .33=h+.4 | | 165u-4= | | 68-2x=79-3x | | t-23.5=39.7 | | 36=(8)-(14x) | | 0.05m=13.80 | | 9.2=-5g-23.3 | | (-3x)-(7)=23 | | 65-x=180 | | 9+2x=49 | | (-3x)-(7)=3 | | [5x]-7=14 | | abs(5x-4)=-6 | | 9x-4=72 | | 15m+6.3=9.8 | | abs(5x-4)=6 | | Y=7.5+0.5x | | 12y=-48+4x |

Equations solver categories